Can Erythropoietin Reduce Hypoxemic Neurological Damages in Neonates With Congenital Heart Defects? - Ottolenghi, Sara; Milano, Giuseppina; Cas, Michele Dei; Findley, Tina O.; Paroni, Rita; Corno, Antonio F. (Frontiers in Pharmacology, 2021)
Congenital heart defects (CHD), the most common cause of birth defects with increasing birth prevalence, affect nearly 1% of live births worldwide. Cyanotic CHD are characterized by hypoxemia, with subsequent reduced oxygen delivery to the brain, especially critical during brain development, beginning in the fetus and continuing through the neonatal period. Therefore, neonates with CHD carry a high risk for neurological comorbidities, even more frequently when there are associated underlying genetic disorders. We review the currently available knowledge on potential prevention strategies to reduce brain damage induced by hypoxemia during fetal development and immediately after birth, and the role of erythropoietin (EPO) as a potential adjunctive treatment. Maternal hyper-oxygenation had been studied as a potential therapeutic to improve fetal oxygenation. Despite demonstrating some effectiveness, maternal hyper-oxygenation has proven to be impractical for extensive clinical application, thus prompting the investigation of specific pathways for pharmacological intervention. Among those, the role of antioxidant pathways and Hypoxia Inducible Factors (HIF) have been studied for their involvement in the protective response to hypoxic injury. One of the proteins induced by HIF, EPO, has properties of being anti-apoptotic, antioxidant, and protective for neurons, astrocytes, and oligodendrocytes. In human trials, EPO administration in neonates with hypoxic ischemic encephalopathy (HIE) significantly reduced the neurological hypoxemic damages in several reported studies. Currently, it is unknown if the mechanisms of pathophysiology of cyanotic CHD are like HIE. Neonates with cyanotic CHD are exposed to both chronic hypoxemia and episodes of acute ischemia-reperfusion injury when undergo cardiopulmonary bypass surgery requiring aortic cross-clamp and general anesthesia. Our review supports future trials to evaluate the potential efficiency of EPO in reducing the hypoxemic neurologic damages in neonates with CHD. Furthermore, it suggests the need to identify early biomarkers of hypoxia-induced neurological damage, which must be sensitive to the neuroprotective effects of EPO.